Pengaruh Content Marketing Dan Influencer Marketing Terhadap Keputusan Pembelian Pada Aplikasi Tiktok (Studi Pada Generasi Z) - Romadhon, Fitra Sasi; Basalamah, Muhammad Ridwan; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to identify and analyze the influence of Content Marketing (X1) and Influencer Marketing (X2) on purchase decisions. The research employs a quantitative approach. The sampling technique used is purposive sampling, with a total of 75 respondents. The respondents in this study are Generation Z students from the Faculty of Economics and Business at the Islamic University of Malang. The data analysis method utilizes statistical tests, including instrument testing, multiple linear regression analysis, normality test, classical assumption test, and hypothesis testing, with analysis conducted using SPSS 30. The results of this study indicate that content marketing and influencer marketing have a significant positive influence, both partially and simultaneously, on purchase decisions. Keywords: Content Marketing, Influencer Marketing, Purchase Decision